Metabolic implications of fiber consumption in children - Weber, Casey Grant (Kansas State University, 2012)
Little is known about the impact of dietary fiber (DF) on children. Current recommendations are based on extrapolations from adult studies. Research is needed to provide science based evidence to determine how DF impacts the gut of children. Two studies were conducted to investigate the interactions of DF in the child large intestine. In the first study, the dose response of DF on breath hydrogen, methane, and total hydrogen content was investigated relative to Institute of Medicine (IOM) recommended intakes in free-living preschool children. Only four of the 18 participants were able to comply with the treatment protocol. Although, no significant differences were noted in breath measures of fermentation across fiber consumption levels, there was a numerical pattern for increasing levels of DF to evolved increased gas production in the four compliers. In free-living individuals measures of acute fiber fermentation through breath was not sensitive enough over 6 hours to distinguish a difference in fermentative rate. Children, parents, and child care centers found this approach apparently acceptable. In study two, the impact of DF (10 g) fed over three weeks in children and their parents on metabolic markers of fermentation were evaluated. The body was able to adapt to 10 g/day DF consumption as bloating (p < 0.05) and flatulence (p = 0.06) decreased each week of the study. Fecal propionic acid was significantly increased over three weeks of DF supplementation. There was also an interaction (p=0.05) between time and age for butyric acid. Dietary fiber supplementation (10 g/day) over three weeks via a commercially available extruded cereal was well-tolerated by the participants, with no disturbances in bowel habit in children or adults. Alternatively, there were no improved bowel habit measures with increased DF consumption. This study provides evidence that this tolerable dose of DF supplementation over three weeks had similar impacts in free-living children and adults. However, the presence of increased butyric acid only in children may be reflective of different production or absorptive capacities between children and adults. Although not presented here, the bacterial ecological analysis may shed further insight into the interactions occurring in the large intestine. These are the first studies to my knowledge to have investigated these outcomes in young children. In addition to the gut health outcomes, this research provided a framework into the apparent feasibility of studying children in a gentle, non-invasive, and cost-effective manner.
Keywords: Gut child fermentation micro biota dietary fiber; Nutrition (0570)